Efek Mediasi Disiplin Kerja pada Peningkatan Kinerja Karyawan oleh Motivasi dan Kompensasi - Supardi Supardi; Teruna Satya Wibawa (Universitas Islam Kadiri, 2022)
Employee performance is one of the most critical factors in boosting corporate performance. The goal of this study was to add work discipline as a mediating variable to the influence of motivation and compensation on employee performance. The research data used was gathered from PT. Truba Garda Device personnel using questionnaires. A sampling of responders was conducted using the sensus method, with a total of 110 employees. The use of SPSS software to test research instruments and path analysis to test hypotheses are examples of data analysis methods. The findings suggest that direct motivation improves employee performance and work discipline, and that motivation influences employee performance via work discipline as a mediating variable. Compensation has a direct impact on work discipline but not on employee performance, and compensation has an indirect impact on employee performance when work discipline is mediated. The corporation can directly raise employee motivation or increase work discipline to improve employee performance, and employee performance through compensation channels must be improved through greater work discipline